Effect of elevated high temperature stress on seed quality of Brassica rapa in ambient storage condition (Journal of Oilseed Brassica, 2026)
In view of the current issue of high temperature stress on seed yield and quality, the present investigation was undertaken to assess the effect of high temperature on seed viability of Brassica rapa during 2017-18 at Assam Agricultural University, Jorhat. Fifteen entries were grown under temperature gradient tunnel (stress) and in the open field (non stress) conditions in randomized block design with two replications. Seed germination percentage and vigour index were observed on the seeds after nine months of storage. Significant variation was observed among the genotypes for germination percentage in stress but not in non-stress condition. For seed vigour index, the genotypes, parents, crosses and parents vs. crosses significantly differed in both stress and non-stress environments. Germination declined by 12 % and seed vigour index by 223 under high temperature stress. Only in stress condition, significant variations for general combining ability (GCA) and specific combining ability (SCA) were observed for germination percentage. Seed vigour index showed significant variations for GCA and SCA effects in both stress and non-stress conditions. Yellow sarson parents exhibited better combining ability for seed quality after storage than the toria parents under high temperature stress.